Magnetic Properties of Coni Nanowires and Nanotubes: Insights from Micromagnetic Simulations and Composition-Dependent Equations - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2023)
We conducted micromagnetic simulations of CoNi nanowires and nanotubes to study their magnetic properties as a function of their composition. We found that the hysteresis curves for isolated CoNi nanowires exhibit a square trend with an easy axis of magnetization along the nanowire axis. The coercivity and normalized remanence show a U-shaped behavior, with maximum values at Ni and Co and minimum values for the Co40Ni60 alloy. The hysteresis curves for CoNi nanotubes maintain the square trend of nanowires, but with a clear decrease in coercivity and an asymmetric V-shaped behavior for coercivity and normalized remanence. Our research offers valuable and comprehensive insights into the magnetic properties of CoNi nanowires and nanotubes. It underscores the significant influence of composition on magnetic properties, which holds great relevance for potential applications. Our approach, involving the prediction of static magnetic properties through micromagnetic simulations and tailored equations designed for nanostructures, rather than relying on bulk parameters, aligns more closely with the nature of these physical systems. This alignment is validated by the strong agreement with previously reported experimental results. Our work lays a solid foundation for the deliberate design of CoNi nanowires and nanotubes with specific magnetic properties tailored for articular applications. We anticipate that our study will facilitate the development of innovative magnetic nanostructures with controllable properties and enhanced performance. © 2023 The Author(s)